2004
DOI: 10.4152/pea.200403279
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of a Textile Dye C. I. Direct Red 80 by Electrochemical Processes

Abstract: The electrochemical removal of the textile dye C. I. Direct Red 80 (DR80) was carried out using three different materials as anodes: iron, polypyrrole (PPy) and boron doped diamond (BDD). Iron electrodes are consumed during the electrolysis, and promote flocculation/coagulation of the dye. Polypyrrole, a conducting polymer, was prepared by chemical/electrochemical precipitation over a cotton cloth; it enables the precipitation of the dissolved dye through a conversion reaction in a less soluble compound. Boron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 17 publications
1
22
0
2
Order By: Relevance
“…Several anode materials, like iron, conducting polymer a boron doped diamond electrode etc., with different experimental conditions, have been used successfully in the electro-degradation of dyes (Dogan and Turkdemir, 2005;Faouzi et al, 2007;Oliveira et al, 2007a). A colour removal (Lopes et al, 2004) of 83-100% was observed for Direct Red 80 using three different electrodes: iron, polypyrrole doped with chromium and boron doped diamond electrode. This technique is effective in decolourisation of soluble and insoluble dyes with reduction of COD.…”
Section: Methods Of Dye Removalmentioning
confidence: 96%
“…Several anode materials, like iron, conducting polymer a boron doped diamond electrode etc., with different experimental conditions, have been used successfully in the electro-degradation of dyes (Dogan and Turkdemir, 2005;Faouzi et al, 2007;Oliveira et al, 2007a). A colour removal (Lopes et al, 2004) of 83-100% was observed for Direct Red 80 using three different electrodes: iron, polypyrrole doped with chromium and boron doped diamond electrode. This technique is effective in decolourisation of soluble and insoluble dyes with reduction of COD.…”
Section: Methods Of Dye Removalmentioning
confidence: 96%
“…Typical examples of widely used anodes include Fe [27], steel [28,29], Al [30], Dimensionally Stable Anodes (DSA) composed of mixtures of Ti, Ir, Ru, Sn, Pb and/or Sb oxides [31][32][33], Pt [29,34] or Tisupported Pt [35], granular activated carbon [14], activated carbon fiber (ACF) [15], glassy carbon [16], graphite [17], polypyrrole [18], perovskite-like BaPb 0.9 Sb 0.1 O 3 [19] and BDD deposited mainly on Si [20], Ti [21] or Nb [7] substrates. These electrodes could be used either for direct (occurring at the surface of the anode) or for indirect oxidation processes such as the homogeneous reaction of organic pollutants with strong oxidants (like active chlorine [36], or hydroxyl radicals via Fenton's reaction [37]).…”
Section: Introductionmentioning
confidence: 99%
“…The employment of polypyrrole coated textiles in the electrochemical removal of the textile dye C. I. Direct Red 80 has been also reported [26]. Polyaniline/MnO 2 catalyst and H 2 O 2 as an oxidant have been employed in the degradation of organic dyes such as Direct Red 81, Indigo Carmine and Acid Blue 92 [27,28].…”
mentioning
confidence: 98%